Comparative histopathology of virulent and avirulent Meloidogyne javanica populations on susceptible and resistant tomato plants - Gabriel, Márcia; Santos, Marcilene F. A.; Mattos, Vanessa S.; Gomes, Ana Cristina M. M.; de Almeida, Sheila F.; Castagnone-Sereno, Philippe; Boiteux, Leonardo S.; Cares, Juvenil E.; Carneiro, Regina M. D. G. (Frontiers in Plant Science, 2024)
The Mi-1.2 gene confers resistance to a wide range of Meloidogyne species, being the most important resistance factor employed in tomato breeding so far. However, many aspects related to the interaction of Mi-1.2-carrying tomato cultivars and virulent/avirulent Meloidogyne populations have not yet been clarified. Herein, comparative histopathological analyses were carried after inoculation of the homozygous (Mi-1.2/Mi-1.2) tomato rootstock 'Guardião' and the susceptible cultivar 'Santa Clara' (mi-1.2/mi-1.2) with virulent and avirulent populations of M. javanica. In the susceptible control, it was possible to visualize second stage juveniles (J2) of avirulent population and feeding sites from 2 to 30 days after infection (DAI) with females reaching maturity at 24-34 DAI. In the resistant rootstock, the Mi-1.2 gene-mediated resistance was related mainly to early defense responses (pre-infection and hypersensitive reaction), which leaed to an immunity-like phenotype that completely prevented the reproduction of the avirulent Meloidogyne population. On the other hand, J2s of the virulent M. javanica population were able to penetrate roots much more than the avirulent population, migrated and developed normally, showing intense and similar pattern of penetration from 4 to 34 DAI in the root tissues of both resistant and susceptible tomato genotypes. The total numbers of J2, J3, J4, and females counted in 'Santa Clara' for the virulent population of M. javanica were higher than in 'Guardião'.